2021
DOI: 10.3390/sym13040588
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Comparison on New (Z)-5-(Azulen-1-Ylmethylene)-2-Thioxo-Thiazolidin-4-Ones

Abstract: Three (Z)-5-(azulen-1-ylmethylene)-2-thioxo-thiazolidin-4-ones are electrochemically characterized by cyclic voltammetry, differential pulse voltammetry, and rotating disk electrode voltammetry. The electrochemical investigations revealed that the redox potential is influenced by the number and position of the alkyl groups, and the possible oxidation mechanism is proposed. These compounds, after their immobilization on glassy carbon electrodes during oxidative electropolymerization, were examined as complexing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In this work, it is shown that such films had the potential to be used for complexing electrochemical sensors based on CMEs. Taking into account the confirmed complexing properties of rhodanine moiety [29,30], the ligands based on benzylidenerhodanine are good candidates to serve as HM sensors for the analysis of HM content in waters.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, it is shown that such films had the potential to be used for complexing electrochemical sensors based on CMEs. Taking into account the confirmed complexing properties of rhodanine moiety [29,30], the ligands based on benzylidenerhodanine are good candidates to serve as HM sensors for the analysis of HM content in waters.…”
Section: Introductionmentioning
confidence: 99%
“…Chemically modified electrodes (CMEs) obtained by electrochemical polymerization of differently substituted azulene monomers have been previously tested and characterized by electrochemistry [1,2]. The previously reported data refer to heavy metals (HMs) ions recognition attempts to detect very low concentrations of contaminants such as cadmium, copper, mercury, chromium, cobalt, nickel, or lead in water [3][4][5].…”
Section: Introductionmentioning
confidence: 99%